Late Holocene tundra fires and linkages to climate and vegetation in Northern Alaska - Lee Frank-DePue; Melissa L. Chipman (Arctic Science, 2025)
Charcoal particles in lake sediments can reveal past fires and linkages to climate and vegetation change. We use analyses of charcoal accumulation rates from two lakes on the Alaskan North Slope to reconstruct past fire activity, and charcoal morphology to identify changes in fuel sources. Charcoal peak analyses were used to calculate individual fire-return intervals (FRIs; years between fire) and mean FRIs (mFRIs) with 95% confidence intervals at local and regional scales. The Lake I4 core (RTS7U2, basal age 7046 cal year B.P.) shows shorter FRIs after ∼3000 cal year B.P. based on the >90 µm charcoal size fraction (regional burning), which coincides with Neoglacial cooling and decreasing moisture. A second higher-resolution core from nearby Kirk Lake (RTS5U3, basal age 743 years) captures short FRIs (mFRI = 198 (105–133) years), suggesting frequent burning compared to the late Holocene portion of Lake I4 core (mFRI = 378 (294–455) years). mFRIs from the larger charcoal size fractions (>125 µm; local burning) at both sites overlap with modern fire cycles observed in the region over the past 82 years. However, the Kirk Lake watershed burned more frequently than other sites in the region, likely related to abundant local shrub cover. These analyses suggest that tundra fires are related to climate variability, but local-scale feedbacks with vegetation can result in heterogenous burning, with implications for ongoing Arctic greening and warming.